Primary Treatment and Prognostic Factors of Carcinosarcoma of the Ovary, Fallopian Tube, and Peritoneum: A Taiwanese Gynecologic Oncology Group Study. Issue 3 (1st March 2014) - Lu, Chien-Hsing; Chen, I-Hui; Chen, Yi-Jen; Wang, Kung-Liahng; Qiu, Jian-Tai Timothy; Lin, Hao; Lin, Wu-Chou; Liou, Wen-Shiung; Huang, Yu-Fang; Lin, Yue-Shan; Tee, Yi-Torng; Hung, Yao-Ching
Abstract : Objective: This study aimed to determine the clinical prognostic factors involved in carcinosarcoma of the ovary, fallopian tube, and peritoneum. Materials and Methods: This retrospective study was undertaken by the Taiwanese Gynecologic Oncology Group. The retrieved clinical data included demographic characteristics, medical disease, tumor status, extent of surgery, and adjuvant chemotherapy. Results: In total, 63 patients with carcinosarcoma of the ovary, fallopian tube, and peritoneum were identified. Sixty-one patients with complete data were enrolled for further data analysis. The mean follow-up period was 1.0 year, and the mean overall survival was 15.4 months. By log-rank tests, age, menopausal status, parity, hypertension, diabetes, primary tumor size, para-aortic lymph node metastasis, pretreatment CA-125, preceding diagnostic surgery, hysterectomy, lymphadenectomy, other surgeries, and paclitaxel use were not predictive of overall survival. Omentectomy, no gross residual implants after surgery, platinum treatment, and no pelvic lymph node metastasis had a trend toward better survival. Early diagnosis at stage I and cisplatin/ifosfamide regimen were significant associated with a better overall survival in log-rank and simple Cox regression tests. Bilateral ovarian tumors and metastatic tumors larger than 2 cm were significantly associated with a poorer overall survival. Conclusions: Early diagnosis at stage I, unilateral ovarian tumor, metastatic tumors less than 2 cm, and cisplatin/ifosfamide regimen were predictive of a better survival. Omentectomy and complete debulking surgery also showed a trend toward better survival. Thus, these treatment strategies should be applied in patients with carcinosarcoma of the ovary, fallopian tube, and peritoneum.